The Impact of Strategic Renewal on Achieving the Resilience of Service Projects: An Analytical Study in the Najaf Governorate Investment Authority - Muntaha Manate Hashim (Indonesian Journal of Law and Economics Review, 2026)
General Background: Rapid environmental changes in developing economies require organizations to adopt adaptive strategies to sustain service project performance. Specific Background: This study examines strategic renewal, comprising content, context, and process dimensions, in relation to service project resilience, including structural, operational, and strategic resilience, within the Najaf Governorate Investment Authority. Knowledge Gap: Prior studies have largely emphasized industrial sectors, with limited analytical focus on the linkage between strategic renewal and resilience in service projects, particularly in the Iraqi context. Aims: The research aims to analyze the relationship between strategic renewal and service project resilience and to evaluate how renewal dimensions relate to resilience dimensions. Results: Using a descriptive-analytical approach with SPSS and SmartPLS on data from 85 respondents, the findings indicate a statistically significant positive relationship between strategic renewal and service project resilience, with varying contributions across dimensions and an explanatory power reaching 66.3% of variance. Novelty: The study presents an integrated analytical model linking multidimensional strategic renewal with resilience dimensions in service projects within a real institutional setting. Implications: The findings support the adoption of periodic renewal of investment portfolios, strengthening partnerships with private and community sectors, and transitioning toward a strategic partnership role to sustain resilient service projects. Highlights:• Strategic renewal dimensions show significant positive relationships with resilience dimensions• Analytical model explains substantial variance in service project adaptability• Institutional recommendations emphasize portfolio renewal and partnership restructuring Keywords: Strategic Renewal, Service Project Resilience, Organizational Adaptation, Investment Authority, Structural Equation Modeling